Therapeutic approaches to potassium disorders - Herrera-Añazco, Percy (2024)
Potassium is an essential cation for multiple physiological processes and potassium disorders, also known as dyskalemias, imply an increased risk of cardiovascular and neurological complications. The present review aims to outline the main strategies for the management of patients with potassium disorders in the hospital setting. For the management of hyperkalemia, we propose that the therapeutic approach should include etiologic evaluation, evidence-based pharmacologic management, monitoring of therapeutic response, and timely decision on initiation of dialysis. For hypokalemia, we suggest initial assessment of severity, pharmacologic management, and monitoring of response to therapy. Despite the limitations of the primary evidence for the management of potassium disorders, the present recommendations emphasize practices based on the best available evidence.